Connectivity and Management of Technological Supplies in Educational Institutions during COVID 19 (Journal of Pharmaceutical Negative Results, 2022)
A documentary review was carried out on the production and publication of research papers related to the study of the variableConnectivity and Management of Technological Supplies in Educational Institutions during Covid-19 in Latin America. The purpose ofthe bibliometric analysis proposed in this document is to know the main characteristics of the volume of publications registered inScopus database during the period between 2020 and the first semester of 2021 in Latin American countries, achieving the identificationof 32 publications in total. The information provided by this platform was organized by means of graphs and figures, categorizing theinformation by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics weredescribed, the position of different authors regarding the proposed topic was referenced by means of a qualitative analysis. Among themain findings of this research, it is found that Mexico, with 10 publications, is the Latin American country with the highest production.The area of knowledge that made the greatest contribution to the construction of bibliographic material related to the study ofConnectivity and Supply Management was Social Sciences with 19 published documents, and the type of publication that was most usedduring the period mentioned above was the journal article, which represents 66% of the total scientific production.